If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15=(c/3)-2
We move all terms to the left:
15-((c/3)-2)=0
We add all the numbers together, and all the variables
-((+c/3)-2)+15=0
We multiply all the terms by the denominator
-((+c+15*3)-2)=0
We calculate terms in parentheses: -((+c+15*3)-2), so:We get rid of parentheses
(+c+15*3)-2
We add all the numbers together, and all the variables
(c+45)-2
We get rid of parentheses
c+45-2
We add all the numbers together, and all the variables
c+43
Back to the equation:
-(c+43)
-c-43=0
We add all the numbers together, and all the variables
-1c-43=0
We move all terms containing c to the left, all other terms to the right
-c=43
c=43/-1
c=-43
| 1/3(6d+3)=4(d-1) | | y=2(9)+4 | | -3x+15=4x-9 | | 0.1x+(3x+20/5)=0.5 | | -4+x÷3=10 | | 15r-6=36 | | 7(x-2)+7=4x+3(-2+3) | | 3x÷5=-10 | | 3|2x+1|=13 | | 7x+13=4x+25 | | 2|3x+1|=13 | | 4=q-15 | | -6g+7=2(-2g+1)-2g-9 | | 2-(-2s)=0 | | 2r-6+5r=3+7r+7 | | 0.1x+0.3+2/0.5=0.5 | | 1×1.01^x=2 | | 0=2y+30 | | v-2=v-11 | | 50x=x^2+500 | | -9+45=6(x-5) | | 2(3x-7)=6x+14 | | 3y(3y-5)(2y-7)=0 | | 13g-5g+-11g-7=5 | | 2x+4x+6x=72 | | 8b+12.3-b=8.1+7b+4.2 | | 11=2(c+2)+3 | | 36+4x=2x-7(1-7) | | a-19=4 | | 2x+4x6x=72 | | -3s+25=25 | | 5n^2+10n-113=7 |